The Influence of Teacher Preparedness on Teaching of Traditional Sports and Games in Physical Education in Public Primary Schools in Machakos County, Kenya - Munyao, Kithuka; Munayi, Simon; Otieno, Michael (African Journal of Education and Practice, 2025)
Purpose: This study investigated the influence of teacher preparedness on teaching of traditional sports and games in physical education in public primary schools in Machakos County, Kenya. Methodology: A descriptive research design was employed, utilizing questionnaires from 322 teachers, and focus group discussions with 32 groups of learners. Stratified random sampling was used to select participants. Descriptive analysis was used, which included means, standard deviation, relative frequencies, and percentages. A computer software programme, Statistical Package for Social Scientists (SPSS) version 21.0, was used for analysis to generate data array that was used for subsequent analysis of the data. Qualitative data was analysed using thematic analysis. Inferential statistics using the Chi-square test was applied to examine the relationship between the research variables. Tables and graphical presentation were used to present the data that was collected for ease of interpretation. The analyzed data was presented using tables. Findings: The findings of the study indicated that teachers have received formal training on teaching TSGs in PE (χ2 = 20.681; df = 1; p = 0.000<0.05), teachers have attended workshops on traditional sports and games (χ2 = 55.546; df = 1; p = 0.000<0.05), and teachers have experience in playing the traditional sports and games that they teach during PE (χ2 = 137.195; df = 1; p = 0.000<0.05). All study investigated teachers’ preparedness factors had p-value < 0.05 therefore confirming that teachers’ preparedness has a significant influence on teaching of traditional sports and games in physical education in public primary schools in Kenya. Unique Contribution to Theory, Practice and Policy: The study recommended providing structured teacher training, and formally incorporating TSGs into the PE curriculum. Also, Teachers should be provided with comprehensive manuals, curriculum outlines, and educational movies to enhance their confidence and expertise.